Methodological strategy for the development of the professionalization of medical education teachers - Geovanis Olivares Paizan; Vivian Walter Sánchez; Rosana Cuello Ho (Revista MENDIVE, 2021)
The process of professionalization of the education professional of the Higher Education in Cuba is a matter that charges particular importance in the context of current development in the world. In this sense, it was identified as objective to propose a methodological strategy to contribute to the process of professionalization of the educational ones of the departments of Technology of the health and Normalization, metrology and administration of the quality. For their execution it was carried out the investigation with 26 educational professionals of these departments of the University Of Medical Sciences Of Santiago from Cuba. By means of the employment of theoretical methods as the analytic-synthetic one and the inductive-deductive one to carry out the approach to the study object. The empiric methods used consisted on the observation, documentary analysis, interviews to education professionals, and the application of the scale of attitude or differential semantic of Osgood. This was directed to measure the affective component (acceptance-rejection) of the educational sampled toward the methodological strategy for the verification of their viability. As a result of the investigation of the thesis of granting a doctorate on professionalization was designed and it implemented a methodological strategy to perfect this process that contributed to their professional development.